Combined Use of Astragalus Polysaccharide and Berberine Attenuates Insulin Resistance in IR-HepG2 Cells via Regulation of the Gluconeogenesis Signaling Pathway - Mao, Zhu-Jun; Lin, Min; Zhang, Xin; Qin, Lu-Ping (Frontiers in Pharmacology, 2019)
Insulin resistance (IR) is likely to induce metabolic syndrome and type 2 diabetes mellitus (T2DM). Gluconeogenesis (GNG) is a complex metabolic process that may result in glucose generation from certain non-carbohydrate substrates. Chinese herbal medicine astragalus polysaccharides and berberine have been documented to ameliorate IR, and combined use of astragalus polysaccharide (AP) and berberine (BBR) are reported to synergistically produce an even better effect. However, what change may occur in the GNG signaling pathway of IR-HepG2 cells in this synergistic effect and whether AP-BBR attenuates IR by regulating the GNG signaling pathway remain unclear. For the first time, we discovered in this study that the optimal time of IR-HepG2 cell model formation was 48 hours after insulin intervention. AP-BBR attenuated IR in HepG2 cells and the optimal concentration was 10mg. AP-BBR reduced the intracellular H2O2 content with no significant effect on apoptosis of IR-HepG2 cells. In addition, a rapid change was observed in intracellular calcium current of the IR-HepG2 cell model, and AP-BBR intervention attenuated this change markedly. The gene sequencing results showed that the GNG signaling pathway was one of the signaling pathways of AP-BBR to attenuate IR in IR-Hepg2 cells. The expression of p-FoxO1Ser256 and PEPCK protein was increased and the expression of GLUT2 protein was decreased significantly in the IR-HepG2 cell model, and both of these effects could be reversed by AP-BBR intervention. AP-BBR attenuated IR in IR-HepG2 cells, probably by regulating the GNG signaling Pathway.